EDUCATIONAL PODCAST ON LEPROSY AS A LEARNING RESOURCE - Ferreira, Mirthis Cordeiro; Costa, Raphael Henrique Gomes da; Muniz, Ricardo Alexandre Amaral; Santos, Carlos Renato dos; Santos, Claudia Benedita dos; Vasconcelos, Eliane Maria Ribeiro de (Cogitare Enfermagem, 2024)
Objective: Evaluate the effect of a podcast as an educational action on Youth and Adult Education (EJA) students in learning about leprosy. Method: Prospective, quasi-experimental study. An educational action was carried out with an educational podcast about leprosy in public schools in Recife, Pernambuco, 2024. The sample consisted of 211 students and the selection was non-probabilistic by convenience. The collection took place through a questionnaire involving content about leprosy, and McNemar was used to assess the significance of the changes. Results: After the intervention, there was an increase in the number of students with adequate knowledge, with the proportion of changes from errors in the pre-test to correct answers in the post-test being greater (p < 0.05) than the proportion of changes from correct answers in the pre-test to errors in the post-test for the questions. Conclusion: Using tools like podcasts in health education enables access and dissemination of information, promoting knowledge and changes in individual and collective health behavior.